Analysis of Shielding Effectiveness of the Cavity Built with Single-Layer Reinforced Concrete - Xiangang Sun; Bing Wei; Yuebo Li; Jie Yang; Liuhong Huang; Jiuliang Xiong (International Journal of Antennas and Propagation)
In view of the existing literature mainly studying the situation of infinite reinforced concrete structure, the shielding effectiveness of three-dimensional single-layer reinforced concrete cavity is studied by considering the structural parameters of steel and the electromagnetic parameters of the concrete. The influence of structure parameters of steel mesh size, the steel diameter, and electromagnetic parameters of concrete dielectric coefficient, conductivity and moisture content on shielding effectiveness of reinforced concrete are analyzed. The research shows that the shielding effectiveness of the reinforced concrete cavity structure has resonance characteristics, and the increase of concrete conductivity and moisture content weaken the resonance characteristics of it so that the shielding effectiveness of the reinforced structure is improved. The results of this paper have a reference value for the analysis of shielding effectiveness of the single-layer reinforced concrete cavity in different practical situations.